NOVAS CONFIGURAÇÕES DAS FAMÍLIAS CONTEMPORÂNEAS: RUPTURAS E/OU CONTINUIDADES NOS DISCURSOS E PRÁTICAS DE METODISTAS E LUTERANOS ACERCA DO DIVÓRCIO E NOVOS CASAMENTOS - Wirth, Noeme de Matos (2014)
In contemporary times, the traditional family (father, mother, children) has undergone a paradigm shift, creating new family configurations with more flexible and pluralistic set-tings. In the new configurations, the constitution element is not only from biological and civil ties, but mainly from the affectivity. In this dissertation, we intend to analyze the disruptions and/or the institutional continuities of religious discourses in the historic Protestantism, spe-cifically in the Methodist and Lutheran Churches, about divorces and remarriages. Through documentary analysis and field research, we aim to identify what impact the new family con-figurations have on the institutional discourse and the ecclesial practice. Our goal is to identify how the religious institutional placement and practice of faith communities are coherent or dissonant before the transformations experienced by the family institution nowadays. The documents used for the analyzes were: the pastorals, official journals, minutes, and other doc-uments that were surveyed in the collections of the UMESP library and the Lutherans Portal. The field research was conducted through questionnaires and interviews to religious volun-teers in the city of Ferraz de Vasconcelos at the Methodist and Lutheran Churches. Through documentary analysis and field research, we seek to identify the impact that the new family configurations caused on the institutional discourse and the ecclesial practice.